Comparative Study of Treatment and Potential Drug Interactions with Mental Disorders Phase at Lampung Psychiatric Hospital - Isnenia, Isnenia; Sembiring, Elma Viorentina (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: There are some phases in mental disorders, acute, stabilization, and maintenance phase. Each phase has a different treatment goal using several types of drugs. Hospitalized patients with mental disorders are typically prescribed 5-9 drugs. Using more than one drug increase the potential for drug interactions.Objectives: This study aims to compare treatments and potential drug interactions with the mental disorders phase at Psychiatric Hospital Lampung Province.Methods: This study was a retrospective with a cohort design. Data were secondary in medical records and inpatient prescription sheets from January to December 2019. Purposive sampling techniques were used. The inclusion criteria in this study were all male patients hospitalized at Psychiatric Hospital Lampung Province who received and completed treatment from January to December 2019.Results: The results showed most of 134 patients were in aged 26-35 years (27.3%), had completed high school (34.3%), were married (61.2%), and were diagnosed with paranoid schizophrenia (93.3%). Average number of medicines was 4.12 in acute phase and 3.89 in stabilization-maintenance phase. Average length of stays were 3.89 days in acute phase and 18.36 days in stabilization-maintenance phase. The second-generation antipsychotics are the most common class of drugs. There was a statistical difference (p = 0.000) for drug classes in both phases. The potential drug interactions in both phases were not significantly different (p = 0.093). The greatest severity was moderate at 88.44% in the acute phase and 94.60% in the stabilization-maintenance phase.Conclusion: There is a statistical difference in drug classes whereas the potential drug interactions were not.